Equivalent heat source approach in a 3D transient heat transfer simulation of full-penetration high power laser beam welding of thick metal plates. (July 2018) - Artinov, Antoni; Bachmann, Marcel; Rethmeier, Michael
Highlights: A novel equivalent volumetric heat source is proposed. Weak constraints and moving mesh were used by the calculation of the thermal cycle. The number of calibration parameters was reduced to one. The standard processing time was reduced to less than 24 h. Abstract: A three-dimensional multi-physics numerical model was developed for the calculation of an appropriate equivalent volumetric heat source and the prediction of the transient thermal cycle during and after fusion welding. Thus the modelling process was separated into two studies. First, the stationary process simulation of full-penetration keyhole laser beam welding of a 15 mm low-alloyed steel thick plate in flat position at a welding speed of 2 m min - 1 and a laser power of 18 kW was performed. A fixed keyhole with a right circular cone shape was used to consider the energy absorbed by the workpiece and to calibrate the model. In the calculation of the weld pool geometry and the local temperature field, the effects of phase transition, thermo-capillary convection, natural convection and temperature-dependent material properties up to evaporation temperature were taken into account. The obtained local temperature field was then used in a subsequent study as an equivalent heat source for the computation of the transient thermal field during the laser welding process and the cooling stage of the part. The system of partial differential equations, describing the stationary heat transfer and the fluid dynamics, were strongly coupled and solved with the commercial finite element software COMSOL Multiphysics 5.0. The energy input in the transient heat transfer simulation was realised by prescription of the nodes temperature. The prescribed nodes reproduced the calculated local temperature field defining the equivalent volumetric heat source. Their translational motion through the part was modelled by a moving mesh approach. An additional remeshing condition and helper lines were used to avoid highly distorted elements. The positions of the elements of the polygonal mesh were calculated with the Laplace's smoothing approach. Good correlation between the numerically calculated and the experimentally observed weld bead shapes and transient temperature distributions was found.